Thickening of the axillary recess capsule on ultrasound correlates with magnetic resonance imaging signs of adhesive capsulitis. (August 2019) - Sernik, Renato A; Vidal Leão, Renata; Luis Bizetto, Eduardo; Sanford Damasceno, Rodrigo; Horvat, Natally; Guido Cerri, Giovanni
Objective: To correlate the thickness of the axillary recess capsule measured by ultrasound with magnetic resonance imaging signs of adhesive capsulitis in patients with shoulder pain. Materials and methods: We prospectively evaluated 193 consecutive patients (141 women and 52 men, aged 40–69 years) with shoulder pain lasting 1–9 months from January 2015 to December 2016 who underwent shoulder ultrasound. All participants had routine shoulder ultrasound with additional measurement of axillary recess capsule thickness. After examinations, two groups were formed: negative ultrasound group, composed of patients with a capsule thickness of 2.0 mm or less, and positive ultrasound group, composed of individuals with a capsule thickness greater than 2.0 mm. All patients from the positive ultrasound group and 27 randomly chosen patients from the negative ultrasound group underwent shoulder magnetic resonance imaging. Results: In all, 169/193 patients (88%) had an axillary recess capsule thickness of 2.0 mm or less (negative ultrasound group) and 24/193 patients (12%) had a capsule thickness greater than 2.0 mm (positive ultrasound group). Twenty-seven patients from negative ultrasound group (27/169) were randomly selected to undergo shoulder magnetic resonance imaging. None of them had magnetic resonance imaging criteria for adhesive capsulitis. All patients from positive ultrasound group (24/24) underwent shoulder magnetic resonance imaging and 23 of them (23/24) had magnetic resonance imaging signs of adhesive capsulitis, with a sensitivity of 100% and a specificity of 96%. Conclusion: In patients with shoulder pain, a thickness greater than 2.0 mm of the axillary recess capsule measured by ultrasound correlates to magnetic resonance imaging signs of adhesive capsulitis with good sensitivity and specificity.